Evaluasi Status Kesuburan Tanah Sawah Sebagai Pendukung Lahan Pertanian Pangan Berkelanjutan di Subak Pagutan dan Tegal Buah Kecamatan Denpasar Barat - RIZKY ALWI SHAH MAULANA; I DEWA MADE ARTHAGAMA; MADE SRI SUMARNIASIH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Evaluation of Paddy Soil Fertility Status as Support of Sustainable Food Farming at Subak Pagutan and Tegal Buah West Denpasar District. Soil fertility is a soil ability for willing substance with enough quantity for plants, for guaranteed willing a Sustainable Food Farming. The research was conducted with purpose to specify the fertility status of the paddy fields at Subak Pagutan and Tegal Buah, West Denpasar District, Denpasar City, with knowing the limitting factor and arranging the directions for the management of land fertility according to the soil limiting factor. The research was conducted using survey methods and soil test methods which did in the Laboratory of Soil and Environmental Sciences, Faculty of Agriculture, Udayana University, parameter which analized for determining the fertility status defined to CEC, BS, C-Organic, P-Total, K-Total with supporting data N-Total, tekstur and soil pH. The limiting factor fertility status in the research location was the low content of C-Organic, P-Total and K-Total. The better-fertility status on subak Pagutan is at SLH III and on subak Tegal Buah is at SLH V. Need returning harvest residue or adding organical addition, and adding fertilizer which contains N, P, K element in single-fertilizer or complex-fertilizer type.